Compendium on the Pilot Study of Special Employment Programmes - Planning Commission (Planning Commission, 1975)
In addition to development programmes included in the Fourth Five Year Plan, certain special employment programmes were implemented during the plan period to make a perceptible impact on the employment situation in the country and to minimise, as far as possible, structural and temporal imbalances in the economy.
Programme Evaluation Organisation Planning Commission Government of India